TINJAUAN KEBUGARAN JASMANI DAN STATUS GIZI SISWA TUNAGRAHITA RINGAN SEKOLAH LUAR BIASA NEGERI 1 LIMAU MANIS PADANG - Mutia Cokes Putri; Hastria Effendi; Bafirman Bafirman (Jurnal Sporta Saintika, 2018)
This research is based on the fact in schools that there are still many students who have a low level of physical fitness, the problem in this study is seen from the activities of students such as students often leave school on the grounds of illness, seem less eager, look lethargic during sports, lack of focus while studying, some even sleepy at the beginning of the class, besides that students tend to like fast food and snacks sold in the canteen. The purpose of this study was to 1) Determine the level of physical fitness and 2) Nutritional status of mild mental retardation students SLB N 1 Limau Manis Padang City. This type of research is descriptive, the population in this study were mild mentally retarded students SLB N 1 Sweet Limau Padang City who were active in the school year 2017-2018. The sampling technique was taken by total sampling, the number of samples in this study was 26 people. Data collection was carried out with the Harvard step up test and BMI test instruments. Data analysis was carried out by descriptive analysis. Physical fitness level of mild mental retardation students SLB N 1 Sweet Limes Padang male city aged 12-18 years obtained 29% good results, 14% enough, 14% less, and 43% less. The level of physical fitness of female mentally retarded students aged 12-18 years and children aged 8-11 years obtained 11% good results, 11% enough, 11% less, and 68% less. Nutritional status of mild mentally retarded students was 4% thin, 69% normal, 15% obese, and 12% obese. To the school, parents, and all parties involved are expected to pay more attention to children's activities and food consumption at school and outside school. Abstrak Penelitian ini didasari pada kenyataan di sekolah bahwa masih banyak siswa yang memiliki tingkat kebugaran jasmani yang rendah, masalah dalam penelitian ini dilihat dari aktivitas siswa seperti siswa sering libur sekolah dengan alasan sakit, tampak kurang bersemangat, tampak lesu saat olahraga, kurang fokus saat belajar, bahkan ada yang mengantuk di jam pelajaran awal, selain itu siswa cenderung suka dengan makanan cepat saji dan makanan ringan yang dijual di kantin. Tujuan penelitian ini adalah 1) Untuk mengetahui tingkat kebugaran jasmani dan 2) Status gizi siswa tunagrahita ringan SLB N 1 Limau Manis Kota Padang. Jenis penelitian ini adalah deskriptif, populasi dalam penelitian ini adalah siswa tunagrahita ringan SLB N 1 Limau Manis Kota Padang yang aktif sekolah tahun pelajaran 2017-2018. Teknik pengambilan sampel di ambil dengan cara total sampling, jumlah sampel pada penelitian ini adalah 26 orang. Untuk pengambilan data dilakuan dengan instrument tes Harvard step up test dan IMT. Analisis data dilakukan dengan analisis deskriptif. Tingkat kebugaran jasmani siswa tunagrahita ringan SLB N 1 Limau Manis Kota Padang putra usia 12-18 tahun diperoleh hasil 29% baik, 14% cukup, 14% kurang, dan 43% kurang sekali. Tingkat kebugaran jasmani siswa tunagrahita putri usia 12-18 tahun dan anak-anak usia 8-11 tahun diperoleh hasil 11% baik, 11% cukup, 11% kurang, dan 68% kurang sekali. Indeksstatus gizi siswa tunagrahita ringan diperoleh hasil 4% kurus, 69% normal, 15% gemuk, dan 12% obesitas. Kepada pihak sekolah, orang tua, dan semua pihak yang terkait diharapkan lebih memperhatikan aktivitas anak dan konsumsi makanan anak disekolah maupun luar sekolah.